PATHOPHYSIOLOGY OF IRRITABLE BOWEL SYNDROME - Makhmudova L.I; Abdullayev I.A (Research Journal of Trauma and Disability Studies, 2024)
The literature review is devoted to the study of factors that occupy an important place in the pathophysiology of irritable bowel syndrome, such as the relationship between the central and enteral nervous system, intestinal barrier function, gene polymorphism, low-level inflammation, imbalance of neurotransmitters and cytokines, as well as changes in the intestinal microbiome.